Investments II: Discussion - Cook, Edgar D. (Journal of Financial and Quantitative Analysis, 1971)
Edgar D. Cook, Jr.*: Harry C. Friedman in his paper, Real Estate Investment and Portfolio Theory, has put his mind to an increasingly important area of financial concern, the relationship of real estate as a security in developing portfolio theory. Between now and the year 2000, it has been estimated that $1,500 billion will be spent on building and remodeling nonfarm housing. There will be an estimated $1,000 billion spent on commercial, industrial, and utility construction. In addition, $1,000 billion will probably be spent on public utilities and service institutions, plus $30 billion annually on community facilities. It is anticipated that each year in coming generations we will add to our existing inventory the equivalent of fifteen cities of 200,000 persons each. Predictions are that there will be a need for an additional 2 million dwelling units per year during the 1970's and that this need will climb steadily thereafter.I